TEMPAT PENGEMBANGAN GRIT - Hans Jonathan; Alvin Hadiwono (Jurusan Arsitektur dan Perencanaan, 2020)
One of the problems in human life is individualism. This is because humans spend too much time at work and at home, so they rarely do social activities, along with the existence of social media that causes people to socialize with each other. This particular problem will be discussed in